2023
DOI: 10.1108/ejm-08-2021-0659
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of advertising: promoting unhealthy food consumption

Bilwa Deshpande,
Puneet Kaur,
Alberto Ferraris
et al.

Abstract: Purpose Scholars have noted the impact of advertising on unhealthy food consumption. However, a systematic literature review (SLR) on this topic is currently lacking. This study aims to find, analyze and synthesize prior literature to set the stage for future researchers and practitioners. It also uncovers research gaps, suggests potential research questions and presents a conceptual framework for use in future research. Design/methodology/approach This paper catalogs and synthesizes topic-related literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 162 publications
0
8
0
Order By: Relevance
“…The most used metric for SB in earlier research has been the amount of time spent watching television, revealing links between TV viewing frequency and cardiovascular risk factors, obesity, metabolic syndrome and type 2 diabetes [ 29 ]. It has been demonstrated that watching TV increases calorie intake, also because of ads promoting foods high in fat, sugar and salt that are increasingly common when viewing TV, which encourage the consumption of these foods [ 30 ]. Furthermore, not only watching TV but also social media use may have some impact on teenagers’ and children’s dietary choices and desires [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most used metric for SB in earlier research has been the amount of time spent watching television, revealing links between TV viewing frequency and cardiovascular risk factors, obesity, metabolic syndrome and type 2 diabetes [ 29 ]. It has been demonstrated that watching TV increases calorie intake, also because of ads promoting foods high in fat, sugar and salt that are increasingly common when viewing TV, which encourage the consumption of these foods [ 30 ]. Furthermore, not only watching TV but also social media use may have some impact on teenagers’ and children’s dietary choices and desires [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advertising consumes an important share of the promotional budget (Sama, 2019) and has a significant impact on consumer behavior (Deshpande et al, 2023;Y. Zhang & Yang, 2023).…”
Section: Gap Analysismentioning
confidence: 99%
“…Analysis of the effects of advertisements and marketing communications on food and nutrition has become an emerging research line [36][37][38]. Various studies have provided evidence on the potential adverse effects of advertising on the consumption patterns of unhealthy foods [9,23,25,38]. Research focused on fast food faces the absence of a universally accepted definition of the concept [39].…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
“…Although advertising for high-energy, low-nutrient foods is associated with an increasing prevalence of obesity across cultures, reactions to these advertising practices vary widely [5,8,49]. In places where obesity is prevalent, fast-food advertising faces scrutiny and stricter regulations are put in place, demanding that companies promote healthy habits and avoid messages that exploit the most vulnerable [38,51]. Conversely, in cultures with traditionally low obesity rates and an emphasis on dietary moderation, advertising has focused less on health and more on the taste and convenience of fast foods [43,44,52].…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
See 1 more Smart Citation